Calitatea vieţii muncitorilor şi clasei mijlocii în Polonia - Misiak, Vladislav (Calitatea Vieții, 1992)
Vladislav Misiak, scientific researcher at the Institute of Sociology belonging to the Wroclav University analyses the phenomena of economic transition in Poland and their social consequences.